Factors Affecting Capital Buffer in Indonesia Islamic Banking by Panel Regression Approach - Erdkhadifa, Rendra; Zenny Nurul Aini Azhari (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2025)
This study is driven by the essential role of the capital buffer in ensuring the financial stability and sustainability of banks. While a high capital buffer enhances stakeholder confidence, it may reduce profit potential due to underutilized funds. Conversely, a low capital buffer may signal higher risk, especially during economic downturns. Thus, analyzing internal factors influencing capital buffer levels in Islamic Commercial Banks is crucial. This research adopts a quantitative method with an associative design. It utilizes secondary data sourced from the annual financial statements of 10 Islamic Commercial Banks in Indonesia covering the years 2019 to 2023, selected through purposive sampling. The data is analyzed using panel data regression, with the common effects model chosen as the most appropriate. The findings indicate that ROA, NPF, and bank size collectively exert a significant influence on the capital buffer. Individually, ROA has a significant positive impact, whereas both NPF and bank size show significant negative impacts. The study concludes that these three factors ROA, NPF, and bank size play a vital role in shaping the capital buffer. These findings highlight the importance for banks to maintain profitability and manage credit risk effectively to support regulatory compliance and stakeholder trust.